Panel cointegration and granger causality approach to foreign direct investment and economic growth in some selected emerging economies - Aderemi Timothy Ayomitunde; Olayemi Henry Omotayo; Akintoye Victor Adejumo; Yusuff Fatai Abolore (European Financial and Accounting Journal, 2019)
The aim of this study is to investigate the relationship between foreign direct investment and economic growth in seven emerging countries. Past empirical studies have failed to estimate the long run relationship between the variables in these countries, which has created a gap in the literature. Data was collected from the United Nations Conference on Trade and Development and World Bank Indicator from 1990 to 2017, and the Johansen Fisher Panel Cointegration and Pairwise Dumitrescu Hurlin Panel Causality Tests were utilised to address the objective of the study. Consequently, the empirical results show that FDI, GDP per capita, growth rate and economic growth have a long run equilibrium relationship. Also, there is an existence of one-way feedback which runs from FDI to economic growth. Based on these findings, this study recommends among others that the policy makers in the emerging countries should ensure the sustainability of the rate of economic growth and embark on more foreign investment-oriented policies that would catalyse further attraction of FDI inflows into their economies.
Keywords: F21; F23; F36; G24; 650; FDI; GDP; Growth Rate; Long Run Relationship and Emerging Countries